2017
DOI: 10.28945/3883
|View full text |Cite
|
Sign up to set email alerts
|

Learning Management System with Prediction Model and Course-content Recommendation Module

Abstract: Aim/Purpose: This study is an attempt to enhance the existing learning management systems today through the integration of technology, particularly with educational data mining and recommendation systems. Background: It utilized five-year historical data to find patterns for predicting student performance in Java Programming to generate appropriate course-content recommendations for the students based on their predicted performance. Methodology : The author used two models for the system development: these a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Given the common use of the LMS in higher education and its importance for teaching and learning, a large body of studies on predictive analytics have used LMS data together with student information from other sources to predict academic performance. In their review, Cui et al (2019) identified several major student-level data sources used in predictive analytics literature, including intermediate course performance, like quiz grades (e.g., Luo, Koprinska, & Liu, 2015), student behaviours in LMSs (e.g., Romero et al, 2013), survey data on socio-emotional variables (e.g., Guarín, Guzmán, & González, 2015), demographic information (e.g., Evale, 2016), and academic history (e.g., Ochoa, 2016). Studies that utilized multiple data sources often showed a high classification accuracy rate.…”
Section: Lms For Learningmentioning
confidence: 99%
“…Given the common use of the LMS in higher education and its importance for teaching and learning, a large body of studies on predictive analytics have used LMS data together with student information from other sources to predict academic performance. In their review, Cui et al (2019) identified several major student-level data sources used in predictive analytics literature, including intermediate course performance, like quiz grades (e.g., Luo, Koprinska, & Liu, 2015), student behaviours in LMSs (e.g., Romero et al, 2013), survey data on socio-emotional variables (e.g., Guarín, Guzmán, & González, 2015), demographic information (e.g., Evale, 2016), and academic history (e.g., Ochoa, 2016). Studies that utilized multiple data sources often showed a high classification accuracy rate.…”
Section: Lms For Learningmentioning
confidence: 99%
“…The learning process can be conducted everywhere and every time, with learning from the internet (e-learning) becoming an integral part of education. E-learning is an effort for giving class instruction and study material in new media that develop the virtual learning era, distance learning, learning management system, content management system, and learning content management (Evale, 2017).…”
Section: Introductionmentioning
confidence: 99%